Insect Responses to Major Landscape-Level Disturbance - Schowalter, T.D (Annual review of entomology, 2012)
Disturbances are abrupt events that dramatically alter habitat conditions and resource distribution for populations and communities. Terrestrial landscapes are subject to various disturbance events that create a matrix of patches with different histories of disturbance and recovery. Species tolerances to extreme conditions during disturbance or to altered habitat or resource conditions following disturbances determine responses to disturbance. Intolerant populations may become locally extinct, whereas other species respond positively to the creation of new habitat or resource conditions. Local extinction represents a challenge for conservation biologists. On the other hand, outbreaks of herbivorous species often are triggered by abundant or stressed hosts and relaxation of predation following disturbances. These insect responses can cause further changes in ecosystem conditions and predispose communities to future disturbances. Improved understanding of insect responses to disturbance will improve prediction of population and community dynamics, as well as ecosystem and global changes.